Role Creation in Opera - Prasauskas, Paulius (Semiotika, 2026)
This article examines the conditions of role creation at the Lithuanian National Opera and Ballet Theatre. It argues that role creation in opera is not only the result of an individual performer’s abilities or artistic choices. It is shaped by a broader set of conditions that includes aesthetic, institutional, and procedural levels. The study is based on the author’s experience of preparing roles at LNOBT between 2022 and 2025. The first part of the article analyses the forms of bodily and vocal expression in opera performances. It shows that at LNOBT the performer’s body is usually shaped according to aesthetic principles that ensure a stable and easily repeatable stage form, while vocal expression remains more dependent on the individual performer’s professional practice. The second part discusses how the performer’s professional status determines their ability to negotiate artistic decisions and working conditions. The third part analyses role creation as the performer’s gradual movement through different theatre spaces. It shows that the more the soloist becomes involved in the collective production process, the more their work is shaped by external demands and the less room remains for individual choice. The study reveals that role creation at LNOBT is shaped by different forms of pressure: the conventions of the opera genre, the power relations of the theatrical field, and the organization of the production process.
Keywords: role creation; opera theatre; emiotics of space; post-Greimassian semiotics; Bourdieu; Fischer-Lichte